The Effect of Inflation and Murabaha on Profitability with NPF as an Intervening Variable - Bahtiar Effendi (Profesional Muda Cendekia Publishing, 2020)
This study aims to determine the effect of inflation, murabaha on the profitability of BPRS mediated by Non Performing Financing (NPF). This study uses quantitative methods and data analysis using Path Analysis with the help of WarpPls 5.0 test tool. Data sources are secondary data obtained from the official website of Bank Indonesia and the Sharia Banking Statistics Report. The results showed that: (1) Inflation did not affect the profitability of BPRS (2) Murabaha financing negatively affect the profitability of BPRS; (3) NPF has a negative effect on profitability of BPRS; (4) Inflation has no effect on NPF of BPRS; (5) Murabahah has a positive effect on NPF of BPRS; (6) NPFs can not mediate the inflation and profitability relationship of the BPRS; (7) NPF mediates the murabahah and profitability of BPRS